Improving Geguritan Reading Skills Using Modeling Method for Students of Class X SMA N 1 Godean - Widiyati, Widiyati; Widayat, Afendy (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to show how the application of modeling method in improving the skill of reading geguritan in Javanese language subject for Class X students of SMA Negeri 1 Godean. This research also aims to show the skill of reading gegurita in Javanese language subject, through modeling method in class X SMA Negeri 1 Godean. The research method used was class action research. Data collection was carried out through observation, interviews, and conducting learning evaluations. Then to facilitate researchers in analyzing the qualitative data obtained, the researchers used a quantitative approach to accompany the modeling learning method. The object of this research is 35 students from class XA SMA Negeri 1 Godean. The results showed that the application of modeling method could improve the skill of reading geguritan. The students of class X SMA Negeri 1 Godean experienced an increase, from an average score of 73.34 to 76.93.